Ethnic Foods Diet Program Improve Self-Efficacy and Diet Compliance Among Type 2 Diabetic Patients - Eka Mishbahatul Mar'ah Has; Amira Aulia; Tiyas Kusumaningrum; Ferry Efendi (Jurnal Ners, 2019)
A well-balanced diet is one of the four pillars of diabetes self-management. Patient's culture strongly influences intake food. Diabetic dietary guidelines which fit with the patient's culture is expected to improve patient's self-efficacy and diet compliance. This study was aimed to analyze the effect of ethnic foods diet program in improving self-efficacy and diet compliance among Type-2 Diabetes Mellitus (T2DM) patients. This was quasy experiment research with pre and post-test control design. The population was 112 T2DM patients from Sasak Tribes, West Nusa Tenggara. Samples were 36 respondents, divided into intervention (18) and control (18) groups. The independent variable was the ethnic food diet (EFD) program, while the dependent variables were patient's self-efficacy and diet compliance. Data were collected using self-efficacy questionnaire and a 24-hour dietary recall form. Data were then analyzed using Wilcoxon Signed Rank Test and Mann Whitney U Test. The result showed differences in self-efficacy between pre and post-test in the treatment group (p=0,001), but there were no differences in the control group. There were differences in diet compliance in the treatment group (p=0,001), but there were no differences in the control group. There were differences between treatment and control groups on self-efficacy (p=0,000) and diet compliance (p=0,000). Ethnic foods diet program can improve self-efficacy and diet compliance among T2DM patients because more comfortable and easier to be applied. Nurses can apply ethnic foods diet program as an intervention to promote healthy diet for T2DM patients.